2018
DOI: 10.1177/1747954118785503
|View full text |Cite
|
Sign up to set email alerts
|

Integrating models of long-term athletic development to maximize the physical development of youth

Abstract: Long-term athletic development is important to prepare youth for sport and an active lifestyle. Several models have provided general frameworks for long-term athletic development from different perspectives that consider factors such as when to sample and specialize and what physical qualities to train and when. More recently, more specific models of long-term athletic development have emerged that focus on both specific modes of training and specific fitness qualities. This includes models focused on the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 73 publications
(206 reference statements)
1
51
0
2
Order By: Relevance
“…Long-term athlete development models provide general frameworks to prepare youth for sports and a physically active lifestyle [1]. These models aim to align practice with growth, maturation, and early sport specialization and to consider factors such as injury risk [2,3] and the limitations of the existing training practice schedules [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Long-term athlete development models provide general frameworks to prepare youth for sports and a physically active lifestyle [1]. These models aim to align practice with growth, maturation, and early sport specialization and to consider factors such as injury risk [2,3] and the limitations of the existing training practice schedules [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Resistance and plyometric training are efficient methods to improve strength, power, speed, and general athleticism in youth athletes [11,12]. Importantly, enhanced physical fitness is a prerequisite for motor competence and technical skill acquisition, in youth athletes [1]. Recently, Lesinski et al [13] demonstrated the positive effects of resistance training (including weight-bearing exercises) on muscular strength and jumping performance in youth athletes, and especially in adolescents, with boys improving more than girls [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leg muscle power and sprinting ability are important performance parameters in several youth sports [1,2]. The effects of training on muscular power and jumping ability are more pronounced in adolescence than childhood, with boys improving more than girls [3].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of training on muscular power and jumping ability are more pronounced in adolescence than childhood, with boys improving more than girls [3]. Adaptations to sprint training are more variable, showing an initial spurt during the ages of 5–9 years, which is followed by a second period of rapid improvement during puberty and beyond [2,4]. A more complex fitness component associated with straight line sprinting, muscular power, and motor coordination, is the change of direction (COD) speed [5].…”
Section: Introductionmentioning
confidence: 99%